Cabaran perlindingan data dalam ekonomi digital (PDPA and the Challenges of Digital Economy) - Zulhuda, Sonny (2017)
The digital economy is here. Malaysia has definitely chosen to embrace it and face the challenges associated with it, especially those in the form of data threats and abuses. Therefore the issue of personal data protection is very timely. This presentation examines those challenges faced by the country, industry and community in the light of the laws on personal data protection in Malaysia. This presentation is part of the Ministry's programmes to educate Malaysian public and data users about Personal Data Protection Act 2010 nation-wide.